Effect of sepiolite clay nanofibers on physical, mechanical, and thermal properties of wood-plastic nanocomposites - Kaymakci, Alperen (SAGE Publications, 2020)
This study was to investigate sepiolite clay nanofibers (SCNs) on some physical, mechanical, and thermal properties of wood-plastic nanocomposites. To meet this objective, pinewood flour with maleic anhydride polypropylene (PP), sepiolite nanofibers (0, 1, 3, 5, and 7 wt%), and PP were compounded in a twin-screw corotating extruder. The mass ratio of the wood flour to PP was 50/50 (wt%/wt%) in all compounds. The test specimens were produced using an injection molding machine from the pellets. Flexural and tensile properties, thickness swelling, water absorption, thermogravimetric analysis, and morphology of the manufactured nanocomposites were evaluated. Based on the findings in this study, flexural and tensile properties of the wood-plastic nanocomposites increased with increasing the content of the sepiolite nanofibers. By increasing the amount of SCNs, thickness swelling and water absorption properties of wood-plastic nanocomposites were improved. Increasing the loading of SCNs increased the amount of residual ash and thermal stability.